Heterocyclic aramid segmented copolymer containing PBO structure, and preparation method and application thereof
By adopting heterocyclic aramid block copolymer with PBO structure and specific spinning technology, the problems of difficulty in preparing PBO fibers and high-temperature decomposition are solved, the mechanical properties of fibers and the stability of production processes are achieved, and the market application field is expanded.
Patent Information
- Application Number
- CN202411779888.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The PBO fiber is difficult to prepare, easy to decompose at high temperatures, and the dynamic viscosity is extremely sensitive to external temperatures, resulting in unstable spinning production process and difficulty in achieving continuous large-scale production.
High-performance fiber products are prepared by using heterocyclic aramid block copolymers containing PBO structures through specific polymerization liquid preparation methods and spinning processes, including blending, filtration, defoaming, spinning metering extrusion, air stretching and heat treatment of heterocyclic aramid polymerization liquid and PBO polymerization liquid.
It improves the mechanical properties of heterocyclic aramid fibers, stabilizes the spinning production process, solves the problems of PBO fiber preparation, and achieves the improvement of fiber performance and the expansion of market application fields.
Smart Images

Figure CN119591886A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of spinning fibers, and specifically relates to a heterocyclic aramid block copolymer containing a PBO structure, a preparation method and an application thereof. Background Art
[0002] Heterocyclic aramid (aramid III fiber) refers to a type of para-aramid containing aromatic heterocycles on the main chain, and the typical aromatic heterocycle is benzimidazole ring. The net tensile strength of the fiber synthesized by ternary polycondensation of p-phenylenediamine, terephthaloyl chloride and benzimidazole diamine can reach 4.5GPa. And it has high thermal stability, and the decomposition temperature of fully aromatic polyamide fiber can reach 550℃. As a reinforcement, the preparation of resin-based high-performance composite materials is one of the most important application areas of aramid. The application range of aramid reinforced resin-based composite materials is very wide, and it plays an important role in many fields such as aerospace, military anti-ballistic, sports equipment, automobiles and construction. The spinning method of heterocyclic aramid usually adopts wet spinning or dry-jet wet spinning. The spinning solution is less disturbed by the outside world, and will not be decomposed at high temperature and affected by fluidity. Therefore, the spinning process parameters are stable, and continuous large-scale production has been realized long ago.
[0003] PBO polymer is a fully aromatic heterocyclic polymer, usually prepared by polycondensation reaction with 4,6-diamino-1,3-resorcinol (DAR) and terephthalic acid (PTA) as monomers. The tensile strength and modulus of its fiber products can reach 5.8GPa and 280GPa respectively. At the same time, it has good heat resistance and stability, and the maximum decomposition temperature can reach 650℃. However, due to the extremely complex spinning process of PBO fiber, the spinning solution is easily disturbed by the outside world, and the decomposition reaction is prone to occur when the temperature is too high. The dynamic viscosity is extremely sensitive to the external temperature. The various process parameters affect each other and are extremely difficult to control. The requirements for spinning equipment are also high, making it difficult to achieve continuous and stable large-scale production. Summary of the invention
[0004] In order to overcome the defects of the prior art, the present invention provides a heterocyclic aramid block copolymer containing a PBO structure, a preparation method and an application thereof, which can solve the technical problems that the current PBO fiber is difficult to prepare, easy to decompose at high temperature, and the dynamic viscosity is extremely sensitive to the external temperature.
[0005] The object of the present invention is achieved through the following technical solutions:
[0006] A heterocyclic aramid block copolymer containing a PBO structure, the structural formula of which is:
[0007]
[0008] In one embodiment, the above-mentioned heterocyclic aramid block copolymer containing a PBO structure is prepared from the following raw materials: a heterocyclic aramid polymer solution and a PBO polymer solution, wherein the heterocyclic aramid polymer solution includes 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine, and terephthaloyl chloride; and the PBO polymer solution includes 4,6-diamino-1,3-resorcinol and terephthalic acid.
[0009] In one embodiment, in the heterocyclic aramid polymerization liquid, the mass ratio of the p-phenylenediamine to the 2-(4-aminophenyl)-5-aminobenzimidazole is 1:(3-3.2), and the mass ratio of the p-phenylenediamine to the terephthaloyl chloride is 1:(4.2-4.8); in the PBO polymerization liquid, the mass ratio of the 4,6-diamino-1,3-resorcinol to the terephthalic acid is 1:(1-1.2).
[0010] The above specific reaction equation is as follows:
[0011]
[0012]
[0013] Finally, block copolymers are generated through the two generated substances.
[0014] In a second aspect, the present invention provides a use of the above-mentioned heterocyclic aramid block copolymer containing a PBO structure in the preparation of fiber products.
[0015] In one embodiment, the preparation of the fiber product comprises the following steps:
[0016] A1, dissolving the heterocyclic aramid block copolymer containing a PBO structure to form a crude slurry;
[0017] A2, filtering and defoaming the crude slurry in sequence to obtain a spinning slurry;
[0018] A3, the spinning slurry is extruded by spinning metering, stretched by air 4.5 to 5.5 times, and then coagulated to obtain primary fibers;
[0019] A4. The spun fibers are washed and dried, and then subjected to primary heat treatment and secondary heat treatment, and then spun to obtain the fiber product.
[0020] In one embodiment, in A3, the coagulation liquid used for coagulation is a 50wt% DMAC aqueous solution; in A4, the drying temperature is 135-145°C, the conditions of the primary heat treatment are: the stretching ratio is 5%, the front and rear fiber tension is 50cN, the drying tunnel temperature is 300°C, and the drying tunnel length is 10m; the conditions of the secondary heat treatment are: the stretching ratio is 5%, the front and rear fiber tension is 50cN, the drying tunnel temperature is 450°C, and the drying tunnel length is 10m.
[0021] In a third aspect, the present invention provides a method for preparing the above-mentioned heterocyclic aramid block copolymer containing a PBO structure, comprising the following steps: preparation of a heterocyclic aramid polymer solution: S1, adding anhydrous lithium chloride to 140-160 ppm of a DMAC solvent and stirring and dissolving the mixture until the LiCl content in the solvent system is 3.2-3.8 wt %; S2, adding 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine, controlling the temperature at 32-38° C., stirring and dissolving for 2 hours and then cooling the mixture to within 5° C.; S3, adding 98-99% of the total mass of terephthaloyl chloride to carry out a prepolymerization reaction; S4, stirring and reacting for 0.9-1.1 hours, and adding the remaining terephthaloyl chloride into the system in three equal portions for telomerization reaction to obtain the obtained product. The heterocyclic aramid polymer solution; preparation of PBO polymer solution: W1, add 4,6-diamino-1,3-resorcinol and terephthalic acid to 140-160ppm of polyphosphoric acid, control the temperature at 105-115°C, and stir and dissolve for 4 hours; W2, control the temperature at 110°C, stir and dissolve for 4 hours, and then add 98.5-99.5% of the total mass of terephthalic acid into the polymerization kettle to carry out prepolymerization reaction; W3, after stirring and reacting for 1 hour, the remaining part of the total mass of terephthalic acid is evenly added into the system for 5 times to carry out polymerization reaction, so as to obtain the PBO polymer solution; preparation of block copolymer polymer solution: the PBO polymer solution and the heterocyclic aramid polymer solution are mixed and stirred for 2 hours to obtain the block copolymer polymer solution.
[0022] In one embodiment, in the heterocyclic aramid polymer solution, the mass concentration of the heterocyclic aramid polymer is 4.5-5.5%, and in the PBO polymer solution, the mass concentration of the PBO is 4.5-5.5%.
[0023] In one embodiment, the dynamic viscosity of the heterocyclic aramid polymer solution is 82,000 to 88,000 centipoise, the dynamic viscosity of the PBO polymer solution is 48,000 to 52,000 centipoise, and the dynamic viscosity of the block copolymer polymer solution is 82,000 to 85,000 centipoise.
[0024] In one embodiment, the mass ratio of the PBO polymer solution to the heterocyclic aramid polymer solution is 1:(8.5-9.5).
[0025] The beneficial effects of the present invention are:
[0026] The present invention can greatly improve the mechanical properties of heterocyclic aramid fibers, stabilize the polymer solution spinning production process, solve the problem that PBO polymer solution spinning production is difficult and cannot be mass-produced continuously, improve the performance of heterocyclic aramid fibers and expand the market application field. It is of great significance to the development of the heterocyclic aramid fiber manufacturing industry and even the entire high-performance organic fiber manufacturing industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be described in more detail below based on embodiments and with reference to the accompanying drawings, wherein:
[0028] Figure 1 It is a schematic diagram of the process of implementing the present invention. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the accompanying drawings.
[0030] Example 1
[0031] This embodiment includes the following steps:
[0032] S1. Add 390 L of DMAC (dimethylacetamide) solvent with a water content of 150 ppm into a 500 L polymerization reactor.
[0033] S2. Add LiCl (anhydrous lithium chloride) with a weight of 14.1 kg into the polymerization kettle containing the solvent, that is, the content of LiCl (anhydrous lithium chloride) in the solvent system is about 3.5 wt%.
[0034] S3. After stirring and dissolving in the polymerization kettle for 0.5 hours, according to the requirement of 5% solid content of the polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) to p-phenylenediamine (PPDA) is 2:1. The material addition amount is calculated by the reaction equation, and 9.41 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and 3.03 kg of p-phenylenediamine (PPDA) are added to the polymerization kettle.
[0035] S4. Control the temperature at 35°C, stir and dissolve for 2 hours, then cool down to less than 5°C.
[0036] S5. According to the requirement of 5wt% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 13.582 kg, is added into the polymerization kettle for prepolymerization.
[0037] S6. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.207 kg, was added to the polymerization reactor in three equal portions to carry out telomerization reaction.
[0038] S7, sampling and testing, the dynamic viscosity is 85,000 centipoise.
[0039] S8. Add 200 L of polyphosphoric acid (PAA) with a moisture content of 150 ppm into another 500 L polymerization kettle.
[0040] S9. According to the requirement of 5 wt% solid content of the polymer material, the molar ratio of 4,6-diamino-1,3-resorcinol (DAR) to terephthalic acid is 1:1. The material addition amount is calculated by the reaction equation, and 5.99 kg of 4,6-diamino-1,3-resorcinol (DAR) is added to the polymerization kettle.
[0041] S10, controlling the temperature at 110°C, stirring and dissolving for 4 hours, calculating the total amount of terephthalic acid (PTA) by the reaction equation according to the requirement of 5wt% solid content of the polymer material, and adding 99% of the theoretical total mass of terephthalic acid, i.e. 7.029kg, into the polymerization kettle for prepolymerization.
[0042] S11. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthalic acid (TPA), i.e., 0.007 kg, was added to the polymerization reactor in 5 equal portions to carry out a telomerization reaction.
[0043] S12. Cool down to 25℃ and take samples for testing. The dynamic viscosity is 50,000 centipoise.
[0044] S13. The two obtained polymer solutions were transferred into a mixing kettle in a mass ratio of 9:1, and blended and stirred for 2 hours to obtain a blended spinning slurry. The dynamic viscosity of the blended spinning slurry was sampled and tested to be 83,000 centipoise.
[0045] S14, filtering and degassing the blended spinning slurry and then transferring it into a spinning section storage tank.
[0046] S15, the spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000dtex, and then air-stretched 5 times through the spinning disk of the dry-jet spinning assembly, and then enters the coagulation bath to form primary fibers. The coagulation liquid is an aqueous solution with a DMAC content of 50wt%.
[0047] S16, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.
[0048] S17. The spun fibers after winding are continuously fed into a two-stage heat treatment drying tunnel through an unwinder and traction rollers. The first-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 5%, a front and rear fiber tension of 50 cN, a drying tunnel temperature of 300°C, and a drying tunnel length of 10 meters. The second-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 5%, a front and rear fiber tension of 300 cN, a drying tunnel temperature of 450°C, a drying tunnel length of 10 meters, and a spinning speed of 20 m / min, thereby obtaining a heterocyclic aramid fiber product containing a PBO structure.
[0049] Example 2
[0050] This embodiment includes the following steps:
[0051] S1. Add 390 L of DMAC (dimethylacetamide) solvent with a water content of 140 ppm into a 500 L polymerization reactor.
[0052] S2. Add LiCl (anhydrous lithium chloride) with a weight of 14.0 kg into the polymerization kettle containing the solvent, that is, the content of LiCl (anhydrous lithium chloride) in the solvent system is about 3.2 wt%.
[0053] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, according to the requirement of 4.5wt% solid content of the polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) to p-phenylenediamine (PPDA) is 2:1. The material addition amount is calculated by the reaction equation, and 9kg of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and 3kg of p-phenylenediamine (PPDA) are added into the polymerization kettle.
[0054] S4. Control the temperature at 32°C, stir and dissolve for 2 hours, then cool down to less than 5°C.
[0055] S5. According to the requirement of 4.5wt% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 12.348kg, is added into the polymerization kettle for prepolymerization.
[0056] S6. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.252 kg, was added to the polymerization reactor in three equal portions to carry out telomerization reaction.
[0057] S7, sampling and testing, the dynamic viscosity is 82,000 centipoise.
[0058] S8. Add 200 L of polyphosphoric acid (PAA) with a moisture content of 140 ppm into another 500 L polymerization kettle.
[0059] S9. According to the requirement of 4.5wt% solid content of polymer material, the molar ratio of 4,6-diamino-1,3-resorcinol (DAR) and terephthalic acid is 1:1, the material addition amount is calculated by the reaction equation, and 6kg of 4,6-diamino-1,3-resorcinol (DAR) is added into the polymerization kettle.
[0060] S10, controlling the temperature at 110°C, stirring and dissolving for 4 hours, calculating the total amount of terephthalic acid (PTA) by the reaction equation according to the requirement of 4.5wt% solid content of the polymer material, and adding 98.5% of the theoretical total mass of terephthalic acid, i.e. 5.91kg, into the polymerization kettle for prepolymerization.
[0061] S11. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthalic acid (TPA), i.e., 0.09 kg, was added to the polymerization reactor in 5 equal portions to carry out telomerization reaction.
[0062] S12. Cool down to 25℃ and take samples for testing. The dynamic viscosity is 48,000 centipoise.
[0063] S13. The two obtained polymer solutions were transferred into a mixing kettle at a mass ratio of heterocyclic aramid polymer solution: PBO polymer solution = 8.5:1, and blended and stirred for 2 hours to obtain a blended spinning slurry. The dynamic viscosity of the sample was 83,000 centipoise.
[0064] S14, filtering and degassing the blended spinning slurry and then transferring it into a spinning section storage tank.
[0065] S15, the spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then air-stretched 4.5 times through the spinning disk of the dry-jet spinning assembly, and then enters the coagulation bath to form primary fibers. The coagulation liquid is an aqueous solution with a DMAC content of 50 wt%.
[0066] S16, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 135°C.
[0067] S17. The spun fibers after winding are continuously fed into a two-stage heat treatment drying tunnel through an unwinder and traction rollers. The first-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 5%, a front and rear fiber tension of 50 cN, a drying tunnel temperature of 300°C, and a drying tunnel length of 10 meters. The second-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 5%, a front and rear fiber tension of 300 cN, a drying tunnel temperature of 450°C, a drying tunnel length of 10 meters, and a spinning speed of 20 m / min, thereby obtaining a heterocyclic aramid fiber product containing a PBO structure.
[0068] Example 3
[0069] This embodiment includes the following steps:
[0070] S1. Add 390 L of DMAC (dimethylacetamide) solvent with a water content of 160 ppm into a 500 L polymerization kettle.
[0071] S2. Add LiCl (anhydrous lithium chloride) with a weight of 14.2 kg into the polymerization kettle containing the solvent, that is, the content of LiCl (anhydrous lithium chloride) in the solvent system is about 3.8 wt%.
[0072] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, according to the requirement of 5.5% solid content of the polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) to p-phenylenediamine (PPDA) is 2:1. The material addition amount is calculated by the reaction equation, and 9.6 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and 3 kg of p-phenylenediamine (PPDA) are added into the polymerization kettle.
[0073] S4. Control the temperature at 38°C, stir and dissolve for 2 hours, then cool down to less than 5°C.
[0074] S5. According to the requirement of 5.5wt% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 99% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 14.256kg, is added into the polymerization kettle for prepolymerization.
[0075] S6. After stirring for 1.1 hours, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.144 kg, was added to the polymerization reactor in three equal portions to carry out a telomerization reaction.
[0076] S7, sampling and testing, the dynamic viscosity is 88,000 centipoise.
[0077] S8. Add 200 L of polyphosphoric acid (PAA) with a moisture content of 160 ppm into another 500 L polymerization kettle.
[0078] S9. According to the requirement of 5.5wt% solid content of polymer material, the molar ratio of 4,6-diamino-1,3-resorcinol (DAR) and terephthalic acid is 1:1, the material addition amount is calculated by the reaction equation, and 6kg of 4,6-diamino-1,3-resorcinol (DAR) is added into the polymerization kettle.
[0079] S10, controlling the temperature at 110°C, stirring and dissolving for 4 hours, calculating the total amount of terephthalic acid (PTA) by the reaction equation according to the requirement of 5wt% solid content of the polymer material, and adding 99.5% of the theoretical total mass of terephthalic acid, i.e. 7.164kg, into the polymerization kettle for prepolymerization.
[0080] S11. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthalic acid (TPA), i.e., 0.036 kg, was added to the polymerization reactor in 5 equal portions to carry out a telomerization reaction.
[0081] S12. Cool down to 25℃ and take samples for testing. The dynamic viscosity is 52,000 centipoise.
[0082] S13. The two obtained polymer solutions were transferred into a mixing kettle in a mass ratio of 9.5:1, and blended and stirred for 2 hours to obtain a blended spinning slurry. The dynamic viscosity of the blended spinning slurry was sampled and tested to be 85,000 centipoise.
[0083] S14, filtering and degassing the blended spinning slurry and then transferring it into a spinning section storage tank.
[0084] S15, the spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000dtex, and then air-stretched 5 times through the spinning disk of the dry-jet spinning assembly, and then enters the coagulation bath to form primary fibers. The coagulation liquid is an aqueous solution with a DMAC content of 50wt%.
[0085] S16, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 145°C.
[0086] S17. The spun fibers after winding are continuously fed into a two-stage heat treatment drying tunnel through an unwinder and traction rollers. The first-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 5%, a front and rear fiber tension of 50 cN, a drying tunnel temperature of 300°C, and a drying tunnel length of 10 meters. The second-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 5%, a front and rear fiber tension of 300 cN, a drying tunnel temperature of 450°C, a drying tunnel length of 10 meters, and a spinning speed of 20 m / min, thereby obtaining a heterocyclic aramid fiber product containing a PBO structure.
[0087] Comparative Example 1
[0088] This comparative example adopts the production process of general heterocyclic aramid fiber, which includes the following steps:
[0089] S1. Add 390 L of DMAC (dimethylacetamide) solvent having a water content of 138 ppm into a 500 L polymerization reactor.
[0090] S2. Add LiCl (anhydrous lithium chloride) with a weight of 14.1 kg into the polymerization kettle containing the solvent, that is, the content of LiCl (anhydrous lithium chloride) in the solvent system is about 3.5%.
[0091] S3. After stirring and dissolving in the polymerization kettle for 0.5 hours, according to the requirement of 5% solid content of the polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) to p-phenylenediamine (PPDA) is 2:1. The material addition amount is calculated by the reaction equation, and 9.41 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and 3.03 kg of p-phenylenediamine (PPDA) are added to the polymerization kettle.
[0092] S4. Control the temperature at 35°C, stir and dissolve for 2 hours, then cool down to less than 5°C.
[0093] S5. According to the requirement of 5% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 13.582 kg, is added into the polymerization kettle for prepolymerization.
[0094] S6. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.207 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.
[0095] S7, sampling and testing, the dynamic viscosity is 80,000 centipoise.
[0096] S8. Filter and deaerate the spinning slurry and then transfer it to the spinning section storage tank.
[0097] S9. The spinning slurry in the storage tank is extruded through spinning metering according to a linear density specification of 1000dtex, and then sprayed into a coagulation bath through a wet spinning component to form spun fibers. The coagulation liquid is an aqueous solution with a DMAC content of 50wt%. The pre-oriented spun fibers are drawn at a stretching ratio of 80% by five rollers before and after the coagulation bath.
[0098] S10, the spun fibers are then washed and dried before being rolled up. The washing water is deionized water and the drying temperature is 140°C.
[0099] S11. The spun fibers after winding are continuously fed into a two-stage heat treatment drying tunnel through an unwinder and traction rollers. The stretching ratio of the first-stage heat treatment drying tunnel is controlled by traction at 5%, the front and rear fiber tension is 50 cN, the drying tunnel temperature is 300°C, and the drying tunnel length is 10 meters. The stretching ratio of the second-stage heat treatment drying tunnel is controlled by traction at 5%, the front and rear fiber tension is 300 cN, the drying tunnel temperature is 450°C, the drying tunnel length is 10 meters, and the spinning speed is 20 m / min.
[0100] S12. After stretching, 1 kg of finished fiber with a line density of 1011 dtex is obtained.
[0101] Comparative Example 2
[0102] In this embodiment, a general PBO fiber production process is used for implementation, including the following steps:
[0103] S1. Add 200 L of polyphosphoric acid (PAA) with a moisture content of 188 ppm into a 500 L polymerization reactor.
[0104] S2. According to the requirement of 5% solid content of polymer material, the molar ratio of 4,6-diamino-1,3-resorcinol (DAR) and terephthalic acid is 1:1. The material addition amount is calculated by the reaction equation, and 5.99 kg of 4,6-diamino-1,3-resorcinol (DAR) is added to the polymerization kettle.
[0105] S3, controlling the temperature at 110°C, stirring and dissolving for 4 hours, according to the requirement of 5% solid content of the polymer material, the total feed amount of terephthalic acid (PTA) is calculated by the reaction equation, and 99% of the theoretical total mass of terephthalic acid, i.e. 7.029 kg, is added into the polymerization kettle for prepolymerization.
[0106] S4. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthalic acid (TPA), i.e., 0.0.07 kg, was added into the polymerization reactor in 5 portions to carry out telomerization reaction.
[0107] S5. Cool down to 25℃ and take samples for testing. The dynamic viscosity is 47,000 centipoise.
[0108] S6. The spinning slurry is filtered and degassed and then transferred to the spinning section storage tank.
[0109] S7. The spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then air-stretched 5 times through the spinning disk of the dry-jet spinning assembly, and then enters the coagulation bath to form primary fibers. The coagulation liquid is an aqueous solution with a content of 50% DMAC.
[0110] S8, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.
[0111] S9. The spun fibers after winding are continuously fed into a two-stage heat treatment drying tunnel through an unwinder and traction rollers. The stretching ratio of the first-stage heat treatment drying tunnel is controlled by traction at 5%, the front and rear fiber tension is 50 cN, the drying tunnel temperature is 300°C, and the drying tunnel length is 10 meters. The stretching ratio of the second-stage heat treatment drying tunnel is controlled by traction at 5%, the front and rear fiber tension is 300 cN, the drying tunnel temperature is 450°C, the drying tunnel length is 10 meters, and the spinning speed is 20 m / min.
[0112] S10. After stretching, 1 kg of finished fiber with a line density of 1051 dtex is obtained.
[0113] Test example
[0114] The fiber finished products obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for fiber modulus, intrinsic viscosity, fiber strength and fiber elongation (the testing conditions refer to GB / T19975-2005 "Test Method for Tensile Properties of High-Reinforced Filaments"). The results are shown in Table 1:
[0115] Table 1 Comparison of results
[0116]
[0117] According to the results in Table 1, the fiber products prepared in Examples 1 to 3 are significantly stronger than the fiber products prepared in Comparative Examples 1 to 2 in terms of fiber strength. This shows that the fiber products prepared in the present invention have a significant advantage in terms of fiber strength.
[0118] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "bottom", "top", "front", "back", "inside", "outside", "left", "right", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0119] Although the present invention is described herein with reference to specific embodiments, it should be understood that these embodiments are merely examples of the principles and applications of the present invention. It should therefore be understood that many modifications may be made to the exemplary embodiments and that other arrangements may be devised without departing from the spirit and scope of the present invention as defined by the appended claims. It should be understood that the various dependent claims and features described herein may be combined in a manner different from that described in the original claims. It should also be understood that features described in conjunction with individual embodiments may be used in other described embodiments.
Claims
1. A heterocyclic aramid block copolymer containing a PBO structure, characterized in that: Its structural formula is:
2. The heterocyclic aramid block copolymer containing a PBO structure according to claim 1, characterized in that: The invention is prepared from the following raw materials: heterocyclic aramid polymer solution and PBO polymer solution, wherein the heterocyclic aramid polymer solution comprises 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine and terephthaloyl chloride; and the PBO polymer solution comprises 4,6-diamino-1,3-resorcinol and terephthalic acid.
3. The heterocyclic aramid block copolymer containing a PBO structure according to claim 2, characterized in that: In the heterocyclic aramid polymerization liquid, the mass ratio of the p-phenylenediamine to the 2-(4-aminophenyl)-5-aminobenzimidazole is 1:3-3.2, and the mass ratio of the p-phenylenediamine to the terephthaloyl chloride is 1:4.2-4.8; in the PBO polymerization liquid, the mass ratio of the 4,6-diamino-1,3-resorcinol to the terephthalic acid is 1:1-1.
2.
4. Use of the heterocyclic aramid block copolymer containing a PBO structure as claimed in any one of claims 1 to 3 in the preparation of fiber products.
5. The use according to claim 4, characterized in that: The preparation of the fiber product comprises the following steps: A1, dissolving the heterocyclic aramid block copolymer containing a PBO structure to form a crude slurry; A2, filtering and defoaming the crude slurry in sequence to obtain a spinning slurry; A3, the spinning slurry is extruded by spinning metering, stretched by air 4.5 to 5.5 times, and then coagulated to obtain primary fibers; A4. The spun fibers are washed and dried, and then subjected to a primary heat treatment, and then spun to obtain the fiber product.
6. The use according to claim 5, characterized in that: In the A3, the coagulation liquid used for coagulation is a 50wt% DMAC aqueous solution; in the A4, the drying temperature is 135-145°C, and the conditions of the primary heat treatment are: a stretching ratio of 5%, a front and rear fiber tension of 50cN, a drying tunnel temperature of 300°C, a drying tunnel length of 10m, and a time of 20-60s; the conditions of the secondary heat treatment are: a stretching ratio of 5%, a front and rear fiber tension of 50cN, a drying tunnel temperature of 450°C, a drying tunnel length of 10m, and a time of 20-60s.
7. A method for preparing a heterocyclic aramid block copolymer containing a PBO structure as claimed in any one of claims 1 to 3, characterized in that: The steps include: Preparation of heterocyclic aramid polymer solution: S1, adding anhydrous lithium chloride to 140-160 ppm of DMAC solvent and stirring to dissolve until the LiCl content in the solvent system is 3.2-3.8 wt%; S2, add 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine, control the temperature at 32-38°C, stir and dissolve for 2 hours and then cool to within 5°C; S3, adding 98-99% of the total mass of terephthaloyl chloride to carry out a prepolymerization reaction; S4, stirring the reaction for 0.9 to 1.1 hours, adding the remaining part of terephthaloyl chloride into the system in three equal portions to carry out a telomerization reaction, thereby obtaining the heterocyclic aramid polymer solution; Preparation of PBO polymer solution: W1. Add 4,6-diamino-1,3-resorcinol and terephthalic acid to 140-160 ppm of polyphosphoric acid, control the temperature at 105-115°C, and stir and dissolve for 4 hours; W2, control the temperature at 110°C, stir and dissolve for 4 hours, then add 98.5-99.5% of the total mass of terephthalic acid into the polymerization kettle to carry out prepolymerization reaction; W3, after stirring and reacting for 1 hour, the remaining part of the total mass of the terephthalic acid is added into the system in 5 equal portions to carry out a telomerization reaction, thereby obtaining the PBO polymerization liquid; Preparation of block copolymer polymerization solution: The PBO polymer solution and the heterocyclic aramid polymer solution are blended and stirred for 2 hours to obtain the block copolymer polymer solution.
8. The method for preparing a heterocyclic aramid block copolymer containing a PBO structure according to claim 7, characterized in that: In the heterocyclic aramid polymer solution, the mass concentration of the heterocyclic aramid polymer is 4.5-5.5%, and in the PBO polymer solution, the mass concentration of the PBO is 4.5-5.5%.
9. The method for preparing a heterocyclic aramid block copolymer containing a PBO structure according to claim 7, characterized in that: The dynamic viscosity of the heterocyclic aramid polymer solution is 82,000 to 88,000 centipoise, the dynamic viscosity of the PBO polymer solution is 48,000 to 52,000 centipoise, and the dynamic viscosity of the block copolymer polymer solution is 82,000 to 85,000 centipoise.
10. The method for preparing a heterocyclic aramid block copolymer containing a PBO structure according to claim 7, characterized in that: The mass ratio of the PBO polymer solution to the heterocyclic aramid polymer solution is 1:8.5-9.5.
Citation Information
Cited By
Preparation method and application of aromatic polyamide fiber with high tensile strength and high compounding property
CN120465137A
High-strength and high-modulus heteroaromatic polyamide fiber and preparation method thereof
CN121363053A